Nitrate in Polluted Mountainous Catchments with Mediterranean Climates - Thomas Meixner; Mark Fenn; Mark Poth (The Scientific World Journal)
The mountains of southern California receive some of the highest rates of nitrogen (N) deposition in the world (~40 kg ha1 year1). These high rates of deposition have translated into consistently high levels of nitrate (NO3) in some streams of the San Bernardino Mountains. However, not all streams are exhibiting these high levels of NO3. Perennial streams have high NO3 concentrations (~200 [b.mu ]moles l1) while ephemeral streams do not (~20 [b.mu ]moles l1). This difference points to groundwater as the source of the NO3 observed in streams. Furthermore, the evidence indicates a differential impact of N deposition on terrestrial and aquatic systems in Mediterranean climates, with aquatic systems being impacted more quickly. The primary reason for this difference involves the asynchrony between the time that atmospheric deposition occurs (summer), the time period of maximum soil NO3 availability and leaching (winter), and the time of maximum plant N demand (spring). Our results indicate that semiarid Mediterranean climate systems behave differently from more humid systems in that, because of this asynchrony, aquatic systems may not be indicative of changes in terrestrial ecosystem response. These differences lead us to the conclusion that the extrapolation of impacts from humid to Mediterranean climates is problematic and the concept of N saturation may need to be revisited for semiarid and seasonally dry systems.